FEMININITY ASPECT AS REFLECTED IN LISA SEE’S SNOW FLOWER AND THE SECRET FAN - Yunie Amalia Rakhmyta (Jurnal As-Salam, 2018)
The purpose of this study is to describe forms opression faced by Chinese women in the nineteenth century as reflected in te novel “Snow Flower and the Secret Fan” written by Lisa See, then to find out the way of the Chinese women to minimize their secluded life. This study is carried out with descriptive research which is collected with documentary technique and used a documentary sheet as the instrument. The finding indicates about the idea of femininity aspect that describes in the oppression faced by Chinese women. This oppression derives into three forms of oppression; emotional oppression, physical oppression, and sexual oppression. The Chinese women try to obey the particular custom judge by the culture to construct the femininity aspect, but secretly they tru to find a way to minimize their secluded life through Nu Shu (secret writing) and having a baby boy. It is hoped that the result of this study will be useful to anyone who wants to study women life situation in a certain communities.